Effects of The Proportion of The LED Light Red, Blue, and White Colors on Chlorophyll Content and Canopy Area of Pakcoy (Brassica rapa L.) - Lestari, Linda Puji Ayu; Wijaya, I Made Anom Sutrisna; Gunadnya, Ida Bagus Putu (Jurnal BETA (Biosistem dan Teknik Pertanian), 2021)
Abstract Light is the main energy source for plants for the photosynthesis process. In indoor cultivation systems (plant factories), LEDs can be used as artificial light. The dominant light colors absorbed by plants for the photosynthesis process are red and blue, but the proportion of the LED colors used is unknown, so it is necessary to research the proportions of light colors. This study aims to determine the effect of the proportions of red, blue, and white light on the chlorophyll content (SPAD value) and the canopy area of Pakcoy. Pakcoy was planted in a growth chamber and given seven different proportions of light for 12 hours with a lamp total of 60 Watt and light intensity of 2000 lux. This study was conducted for 49 days, and the observations to make once a week. The results showed the proportion of red, blue, and white LED light treatment affects the chlorophyll content and canopy area. The proportions of LED light 30 Watt red, 20 Watt blue, and 10 Watt white produced the highest chlorophyll content (35.0 SPAD value) and canopy area (70.7 cm2). In conclusion, the proportion of red, blue, and white LED light showed significantly different in the growth of Pakcoy.